Differential Expression of Cell Wall Remodeling Genes Is Part of the Dynamic Phase-Specific Transcriptional Program of Conidial Germination of Trichoderma asperelloides - Maggie Gortikov; Elizabeta Yakubovich; Zheng Wang; Francesc López-Giráldez; Yujia Tu; Jeffrey P. Townsend; Oded Yarden (Journal of Fungi, 2022)
The nature of saprophytic and mycoparasitic hyphal growth of Trichoderma spp. has been studied extensively, yet its initiation via conidial germination in this genus is less well understood. Using near-synchronous germinating cultures of Trichoderma asperelloides, we followed the morphological progression from dormant conidia to initial polar growth to germling formation and to evidence for first branching. We found that the stage-specific transcriptional profile of T. asperelloides is one of the most dynamic described to date: transcript abundance of over 5000 genes—comprising approximately half of the annotated genome—was unremittingly reduced in the transition from dormancy to polar growth. Conversely, after the onset of germination, the transcript abundance of approximately a quarter of the genome was unremittingly elevated during the transition from elongation to initial branching. These changes are a testimony to the substantial developmental events that accompany germination. Bayesian network analysis identified several chitinase- and glucanase-encoding genes as active transcriptional hubs during germination. Furthermore, the expression of specific members of the chitin synthase and glucan elongase families was significantly increased during germination in the presence of Rhizoctonia solani—a known host of the mycoparasite—indicating that host recognition can occur during the early stages of mycoparasite development.